Darker female pigeons transmit more specific antibodies to their eggs than do paler ones. (9th January 2013) - Jacquin, Lisa; Haussy, Claudy; Bertin, Claire; Laroucau, Karine; Gasparini, Julien
<x xml:space="preserve">Abstract</x> Melanin‐based coloration is widespread among vertebrates, yet the adaptive significance of such pigments remains elusive, particularly with regard to the link between melanin and immune‐mediated maternal effects. The aim of this study was to investigate whether melanin‐based coloration could signal the ability of mothers to mount a humoral response and to transfer maternal antibodies (Ab) to their young. We injected differently coloured (pale and dark) female feral pigeons (Columba livia) with Chlamydiae (a natural antigen) and Keyhole Limpet Haemocyanin (KLH, an artificial antigen), and found no significant difference in humoral response between differently coloured females. However, darker females transferred more Ab against Chlamydiae into their eggs than paler ones, despite similar circulating levels of Ab. In addition to this, melanin‐based coloration showed a high heritability value. This suggests that a genetically based coloured trait might be linked to the ability of females to transfer specific Ab against Chlamydiae (but not against KLH) to their offspring, independent of their ability to produce Ab. This suggests that transmission of maternal Ab is antigen dependent, and that melanin‐based coloration might signal female ability to transmit specific Ab against natural pathogens. © 2013 The Linnean Society of London